STRATEGI KOMUNIKASI DINAS PARIWISATA, KEPEMUDAAN DAN OLAHRAGA, DAN KEBUDAYAAN KABUPATEN INDRAGIRI HILIR DALAM MENARIK MINAT PENGUNJUNG OBJEK WISATA PANTAI SOLOP - Vini Fitri Meilisa; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Indragiri downstream district has some tourist attraction that is well known to the public, especially the people of Riau, one of which is the beach solop. This beach has its own uniqueness that is a swampy / white sandy mud area formed from shells and sea plants brought by the waves to the shore and beautiful mangrove forest surround the solop beach. The government has made various efforts to improve tourism facilities and promotions in order to attract visitors who come to the beach solop. This shows the government's seriousness to develop solop beach tourism. The purpose of this research is to know the communicator strategy, strategy to determine the audience, message strategy and media strategy that used by the Department of Tourism, Youth and Sports and Culture of Indragiri Hilir regency.This research uses qualitative methods, data collection techniques used in this study are interviews, observation and documentation. The subject of informan chosen by purposive sampling technique, which become informan in this research amounted to 8 people that is, 4 people from the Department of Tourism, youth and sports and culture of downstream Indragiri district and 2 people and 2 community members. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations using the technique of validity checking data that is extend participation and triangulation.The results of this research are; that the strategy communicator conducted by the Department of Tourism, Youth and Sports and Culture district Indragiri Hilir has four stages, namely planning, Proposal / endorsement, technical preparation, and implementation of the program and select communicators who have credibility and knowledge, communicant strategy is to determine the primary audience and secondary audiences. The message strategy is by emphasizing the message core and organizing the message. The media strategy is to use print, electronic and internet media.Keyword: Communication Strategy, Solop Beach